Evaluation of Different Levels of Process Energy in Sorghum and Wheat-Based Diets on the Growth Performance of Pacific White Shrimp, Litopenaeus vannamei - Tucker Graff; Trinh Ngo; Donald Allen Davis; Sajid Alavi (Aquaculture Nutrition)
This research evaluated the effect of different levels of extrusion process energy during the production of wheat and sorghum-based feeds on the growth performance and digestibility of Pacific white shrimp (Litopenaeus vannamei). Process energy consisted of mechanical and thermal components, which were both modulated via varying preconditioner steam addition. Diets were formulated to be isonitrogenous (36% protein) and isolipidic (8% fat), with three levels of thermal energy (TE) input during preconditioning (high, medium, and low). All diets showed increased starch gelatinization with increased TE, with the wheat-based diets undergoing a greater degree of gelatinization than the sorghum-based diets. There were no significant differences in final biomass, weight gain, feed conversion ratio (FCR), or survival among the different treatments. However, digestibility results showed that wheat-based diets had significantly higher apparent digestibility coefficients (ADCs) for both protein and energy compared to sorghum-based diets. Overall, increased starch gelatinization that correlated with greater digestibility was observed, but this effect was reduced in the sorghum-based diets. These findings suggest that sorghum can be used as a viable alternative to wheat in shrimp feed without negatively impacting their growth performance, while also offering potential cost savings to producers.